Characterization of hLF1-11 immobilization onto chitosan ultrathin films, and its effects on antimicrobial activity - Fabiola Costa (2014)
hLF1-11 (GRRRRSVQWCA) is an antimicrobial peptide (AMP) with high activity against methicillin-resistant Staphylococcus aureus (MRSA), the most prevalent species in implant-associated infection. In this work, the effect of the surface immobilization on hLF1-11 antimicrobial activity was studied. Immobilization was performed onto chitosan thin films as a model for an implant coating due to its reported osteogenic and antibacterial properties. Chitosan thin films were produced by spin-coating on gold surfaces. hLF1-11 was immobilized onto these films by its C-terminal cysteine in an orientation that exposes the antimicrobial activity-related arginine-rich portion of the peptide. Two levels of exposure (with and without a polyethylene glycol (PEG) spacer) were analyzed. Covalent immobilization was further compared with the AMP physical adsorption onto chitosan films. Surfaces were characterized using ellipsometry, contact angle measurements, atomic force microscopy, infrared and X-ray photoelectron spectroscopies and using a fluorimetric assay for hLF1-11 quantification. Surface antimicrobial activity was assessed through surface adhesion and viability assays using an MRSA (S. aureus ATCC 33591). The incorporation of hLF1-11 increased significantly bacterial adhesion to chitosan films. However, the presence of hLF1-11, namely when immobilized through a PEG spacer, decreased the viability of adherent bacteria with regard to the control surface. These results demonstrated that hLF1-11 after covalent immobilization by its cysteine can maintain activity, particularly if a spacer is applied. However, further studies, exploring the opposite orientation or the same C-terminal orientation, but non-cysteine related, can help to clarify the potential of the hLF1-11 immobilization strategy.